Influence of bull exposure on the behavioural intensity of estrus in Sahiwal heifers (Bos Indicus) - Choudhary, Sanjay; Kamboj, M L; Raheja, Nitin; C, Kotresh Prasad; Singh, Pawan; Kumar, Nishant; Barman, Deepandita; Bhakat, Mukesh (Indian Journal of Dairy Science, 2019)
Present study was conducted to study the influence of presence of bull on the behavioural signs of estrus expressed by Sahiwal heifers. For this experiment, a total of 24 Sahiwal heifers were allotted to 3 groups (T0, T1 and T2) of 8 animals each, based on the age and body weight. In T0, the heifers were isolated from the bull; in T1 group, the heifers were in contact with the bull through a fenceline exposure and in T2 group, the heifers were exposed through a fenceline contact (24 hours) with bull along with direct contact (for 6 hours) through another bull in the heifer shed. Estrus detection was done by bulls in T1 and T2 heifers group whereas in T0 group, heifers heat expectancy chart and visual observation of behavioural signs of estrus were used for estrus detection. Overall mean intensity of sniffing/licking, tail raising, micturition, chin resting and allowing mounting attempts during silent estrus in T0 was largely weak (88.64%) and in T1 heifers group, intensity was weak to moderate (60.05 and 34.58 %) whereas in T2 group, percentage of weak, moderate and intense was 38.5 %, 27.0 % and 34.4 % respectively. The per cent mean intensity of estrus behaviour in second estrus was weak to moderate (71.875 and 28.12) in T0, whereas in T1 group, intensity was largely weak to moderate (42.9 % and 41.3%) and intensity of cardinal signs of estrus in T2 was mostly moderate to intense in nature (31.9 % and 57.7%). It can be concluded that bull biostimulation of Sahiwal heifers through direct contact plus fenceline contact was more effective in increasing estrus behaviour intensity as compared to the only fenceline contact. Most prominent cardinal symptoms of estrus in biostimulated as well as non-biostimulated Sahiwal heifers were sniffing and licking, micturition, tail raising, allowing mounting attempts and chin resting.